Academic Culture and Service Excellence as Predictors of Student Trust: A Case Study at Mandalika University of Education - Suhardi, Muhamad; Zinnurain, Zinnurain (AL-ISHLAH: Jurnal Pendidikan, 2026)
Academic culture and service excellence are widely recognized as key determinants of students’ trust, which in turn shapes educational experiences and persistence in higher education. This study investigates their influence on students’ trust at the Mandalika University of Education (UNDIKMA) Mataram during the odd semester of the 2024/2025 academic year.A descriptive verification design with a survey approach was employed. The sample comprised 100 students from the Faculty of Education and Psychology, purposively selected from the 1st, 3rd, 5th, and 7th semesters. Data were analyzed using descriptive statistics, multiple linear regression, correlation analysis, classical assumption tests, and hypothesis testing with SPSS 21.0.The findings indicate that academic culture and service excellence jointly exert a significant positive effect on students’ trust in completing their studies at UNDIKMA. Both variables demonstrate meaningful contributions, confirming their role as predictors of trust.Strengthening academic culture and improving service excellence are critical for fostering students’ trust and sustaining their commitment to academic completion. Continuous institutional efforts involving all academic stakeholders are necessary to enhance these dimensions and maintain student trust across academic years.